The Nature of Charge-Transfer Excited States in Transition Metal Complexes Pertinent to Energy Conversion and Chemical Sensing - Katz, Néstor Eduardo (2020)
We present procedures for determining the nature of charge-transfer excited states in transition metal complexes relevant to energy conversion and chemical sensing processes. In particular, we analyze the importance of resorting to both spectroelectrochemical and photophysical techniques to elucidate the "fingerprints" of the intermediates involved in the fate of these reactions. Our contributions to the subject are discussed.